Implementasi Aplikasi Baca dan Tulis Sebagai Upaya Peningkatan Literasi Digital - Nurfaizah Nurfaizah; Nandang Hermanto; Agung Tri Wibowo; Fathuzaen Fathuzaen; Hasri Akbar Awal Rozaq (Paradigma - Jurnal Komputer dan Informatika, 2022)
The development of the digital world that continues to increase at this time makes people accustomed to the concept of digitization and technology, even now it has become a necessity. These developments need to be balanced with encouragement for users to better utilize the use of technology through the role of digital literacy. One of the efforts made to encourage the creation of digital literacy is by utilizing technology to support activities that can increase knowledge and improve people's reading and writing literacy. This will make technology users better at using technology and provide other benefits in increasing digital literacy, where increasing digital literacy is currently one of the government targets that has been pursued in various activities to build a society that is not only technology users but also able to utilize technology through their cognitive abilities such as writing so that they are not only able to operate technological devices. This research focuses on making reading and writing applications that can be used by all technology users so that they can foster public interest in reading and writing. In addition, this application will also provide a solution to the sluggish growth of book sales by publishers through the marketplace. Application users can enjoy reading and writing anywhere and anytime and make it easier to search and purchase literacy books. This application was developed using waterfall software development and has gone through a testing stage where all the designed features are already running as specified.